Microencapsulation of limonen oil for textile application - Rodrigues, S.N. (2011)
The production of polyurethane-urea microcapsules using the interfacial polymerization technology was performed. Microcapsules were produced in a basic IKA® Miniplant laboratory reactor, in order to produce microcapsules with controlled parameters. In this formulation, limonene, a fragrant chemical characteristic of the lemon oil - was microencapsulated, because lemon oil is the most used oil in perfumery. It resulted in microcapsules with bimodal distribution and average size equal to 10µm. The characterisation of the microcapsules includes particle size distribution, optical microscopy and scanning electron microscopy. Using scanning electron microscopy it is visible the presence of well defined microcapsules on the woven.